Integrating Parent’s Contribution into Music Class to Achieve Learning Purpose of Musical Expression (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2018)
Qualitative research has been carried out with the aim of exploring synergy between parents and school in elementary school music education in an urban area. The focus of the research is the synergy pattern of parents and school related to students’ music education. In order to derive the findings, one major attention of the research is parent’s contribution integrated into music class to gain a successful learning goal of musical expression. This paper discusses characteristic of the contribution processes in supporting the successful of music learning related to education components of learning material, facility and supporting the budget, with the topic of playing an ensemble of a particular music instrument. The school’s samples chosen were those which are located in a particular urban area in Central Java. The data were gathered using observation, interview and documentation methods and analyzed descriptively. Based on the data analysis, it was concluded that parent’s contribution is an important element for attaining a qualified students’ achievement of musical expression. It is integrated into learning sessions fulfilling the criteria stated in the used curriculum implemented by the teacher, by three major ways, those are communication, collaboration and cooperation. This becomes a significant reason for its integration into elementary school music instruction to achieve the expected students’ competence.